Development Of Kalang Sunda Dance Movements For Upper Elementary School Students: - Alunia, Aulia Ratu Assifa; Wakih, Agus Ahmad; Mahendra, Hatma Heris (CV. Generasi Insan Rafflesia, 2025)
This study aims to develop Kalang Sunda dance movements to align with the motor and cognitive abilities of elementary school students while enhancing their interest in traditional dance art. Kalang Sunda dance was chosen due to its philosophical values and educational potential relevant to students' character development. The research method employed was Research and Development (R&D) using the 4D model (Define, Design, Develop, Disseminate). The subjects consisted of three fifth-grade students at SDN 8 Singaparna, Tasikmalaya Regency. The results showed that the modified movements of the Kalang Sunda Jaipongan creative dance were successfully adapted to students' characteristics, including simplified basic movements and adjusted music tempo. The fun learning and scaffolding approaches proved effective in improving students' abilities, with practice focus duration increasing from 15 minutes to over 30 minutes. Additionally, the incorporation of pencak silat elements successfully broke gender stereotypes and attracted male students' interest. Validation by dance practitioners, extracurricular instructors, and classroom teachers confirmed the product's feasibility with an average score of 80% (